A high-elongation and high-tensile additive and its preparation method and use method
By using three sets of dispensing recipes and tetrahydrothiazolethione homemade dispersions in the production of lithium battery copper foil, the problem of difficulty in taking into account the tensile strength and elongation stability in the existing technology is solved, and the lithium battery copper foil with high tensile strength and high elongation is achieved, which improves the safety and service life of the battery.
Patent Information
- Application Number
- CN202211209526.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-09-30
AI Technical Summary
In the production of lithium-battery copper foil, it is difficult to take into account the stability when improving the tensile strength and elongation, and the tensile strength and elongation index are prone to fluctuations.
A three-component formula is adopted: brightness leveling agent, high antigen and stabilizer, combined with tetrahydrothiazolethione homemade dispersion. Through the combination and use of these components, the tensile strength and elongation of the copper foil are enhanced while maintaining stability.
The high tensile strength (≥500Mpa) and high elongation (≥15%) of lithium battery copper foil are achieved, while reducing surface roughness and improving battery safety and service life.
Abstract
Description
Technical Field
[0001] The invention relates to a high-elongation and high-tensile strength additive and a preparation method and a use method thereof, belonging to the technical field of electrolytic lithium copper foil. Background Art
[0002] At present, copper foil is a key material for manufacturing lithium-ion batteries. The development of its production technology and the quality of its quality will directly affect the manufacturing process, performance and production cost of the battery, especially the tensile strength and elongation of copper foil. If these indicators are low, it will cause the battery pole or copper foil to break. In addition, during the electrochemical cycle of lithium batteries, due to the generation and development of stress, copper foil with low indicators is easily affected by stress, resulting in depression, wrinkles, and even fracture of the copper foil surface, which ultimately increases the internal resistance of the battery and affects the safety and service life of the battery. As the requirements for battery energy storage become higher and higher, the thickness of lithium battery copper foil for negative electrode materials is also required to be thinner and thinner, which requires copper foil to have stronger mechanical properties to a greater extent. From this, it can be seen that high tensile and high elongation copper foil is an inevitable trend in the future.
[0003] The existing additive technology in the production of lithium battery copper foil often improves the tensile strength, but the elongation stability is poor and will drop significantly. If high elongation index is pursued, the tensile strength will also fluctuate greatly.
[0004] In view of the above-mentioned defects, the designers have actively carried out research and innovation in order to create a high-elongation and high-tensile additive and its preparation method and use method, so as to make it more valuable for industrial use. Summary of the invention
[0005] In order to solve the above technical problems, the present invention discloses a high-elongation and high-tensile additive and its preparation method and use method. The formula is three components, namely, a bright leveling agent, a high-resistance agent, and a stabilizer. The bright leveling agent is used to stabilize the brightness and roughness of the foil surface, the high-resistance agent is used to improve the tensile strength of the copper foil, and the stabilizer is used to maintain and improve the elongation when improving the tensile strength. The three components are used in combination, and a self-made dispersion of tetrahydrothiazolidinethione is added. While stabilizing the elongation, it offsets part of the loss of tensile strength. The lithium battery copper foil prepared by adding this additive has the advantages of high tensile strength, high elongation, and low roughness. It has been measured that the tensile strength after baking at a high temperature of 140 degrees Celsius is ≥500Mpa, and the elongation is ≥15%.
[0006] A high-elongation and high-tensile additive of the present invention comprises a brightening and leveling agent, a high-resistance agent and a stabilizer;
[0007] The raw materials of the brightening and leveling agent include one or more of sodium polydisulfide propane sulfonate, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, sodium 3-mercaptopropane sulfonate, sodium phenyl polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, aqueous collagen solution, and polyvinyl pyrrolidone;
[0008] The high resistance agent is composed of amine derivatives and thiourea derivatives;
[0009] The stabilizer consists of a high resistance stabilizer and an extension stabilizer.
[0010] Furthermore, the preparation method of the collagen aqueous solution is: collagen, ethylenediaminetetraacetic acid and water are mixed in a mass ratio of 20:1:179, loaded into a stirring device, stirred and mixed at a speed of 200-300 r / min for 20-30 minutes, and the collagen aqueous solution is obtained after the stirring and mixing is completed.
[0011] Further, the amine derivative raw material includes one of polyethyleneimine alkyl salt, polyethyleneimine alkyl compound, polyacrylamide, and polyquaternary ammonium salt;
[0012] The thiourea derivative raw material includes one of diethylthiourea, allylthiourea, ethylenethiourea and isopropylthiourea.
[0013] Furthermore, the raw material of the high-resistance stabilizer includes one of a homemade tetrahydrothiazolidinethione dispersion and sodium thiazoline dithiopropane sulfonate;
[0014] The raw material of the extension stabilizer includes one or more of polyethylene glycol, allyl polyethylene glycol, fatty amine polyoxyethylene ether, hydroxyethyl cellulose, and fatty alcohol polyoxyethylene ether.
[0015] Furthermore, the preparation method of the homemade thiazolidinethione dispersion is as follows: thiazolidinethione and concentrated sulfuric acid are mixed at a mass ratio of 1:10 to obtain a mixed solution, the mixed solution is mixed with water at a mass ratio of 1:8, and then allyl polyethylene glycol of the same mass as thiazolidinethione is added, and the mixture is placed in an ultrasonic oscillator, and ultrasonically oscillated and mixed at a frequency of 30 kHz for 15 to 20 minutes to obtain a homemade thiazolidinethione dispersion.
[0016] A method for preparing a high-elongation and high-tensile-resistance additive comprises the following specific steps: evenly mixing a brightening and leveling agent, a high-resistance agent and a stabilizer in equal volume ratios to obtain the high-elongation and high-tensile-resistance additive.
[0017] Furthermore, the preparation method of the bright leveling agent is:
[0018] (1) Collagen, ethylenediaminetetraacetic acid and water are mixed in a mass ratio of 20:1:179, and then loaded into a stirring device, and stirred and mixed at a speed of 250 r / min for 25 minutes, and after the stirring and mixing is completed, a collagen aqueous solution is obtained;
[0019] (2) Sodium polydisulfide propane sulfonate, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate and the above collagen aqueous solution were mixed in a mass ratio of 2:1:50 and loaded into a stirring device. After stirring and mixing at a speed of 55 r / min for 35 minutes, a brightening and leveling agent was obtained.
[0020] Furthermore, the preparation step of the high resistance agent is: diethylthiourea and polyethyleneimine alkyl salt are mixed in a mass ratio of 1:15 and put into a stirring tank, and stirred and mixed at a speed of 250r / min for 25min, and the high resistance agent is obtained after the stirring and mixing is completed.
[0021] Furthermore, the preparation steps of the stabilizer are:
[0022] (1) Thiathiazolidinethione and concentrated sulfuric acid were mixed at a mass ratio of 1:10 to obtain a mixed solution, the mixed solution was mixed with water at a mass ratio of 1:8, and then allyl polyethylene glycol of the same mass as that of tetrahydrothiazolidinethione was added, and the mixture was placed in an ultrasonic oscillator and ultrasonically oscillated and mixed at a frequency of 30 kHz for 18 minutes to obtain a self-made tetrahydrothiazolidinethione dispersion;
[0023] (2) A self-made tetrahydrothiazolidinethione dispersion, allyl polyethylene glycol, fatty amine polyoxyethylene ether and hydroxyethyl cellulose were mixed in a mass ratio of 50:1:1:1 and placed in a stirring tank. The mixture was stirred at a speed of 150 r / min for 18 min to obtain a stabilizer.
[0024] Furthermore, the specific application steps are as follows: adding a high elongation and high tensile strength additive to a copper foil electrolyte at an addition amount of 0.5 mL / L, electrolyzing a lithium copper foil, taking out the copper foil after the electrolysis is completed, and baking it at 140°C for 15 minutes to obtain a finished electrolytic copper foil; the parameters of the copper foil electrolyte are as follows: a copper ion concentration of 85 g / L, a sulfuric acid concentration of 100 g / L, a chloride ion concentration of 20 mg / L, and an electrolyte flow rate of 50 m / L during electrolysis. 3 / h, current density 20000A / m 2 .
[0025] By means of the above scheme, the present invention has at least the following advantages:
[0026] (1) The present invention uses a compound containing a sulfur group as a brightener, which can form a cuprous complex and adsorb on the copper deposition site, catalyzing and promoting deposition, thereby reducing the roughness of the copper foil within a certain concentration and increasing the tensile strength and elongation; the presence of amine organic matter in the high-resistance agent can promote the adsorption of cations at the active site, enhance the adsorption of unsaturated bonds, and increase cathode polarization, thereby reducing the surface micro-profile fluctuations, reducing the surface roughness, and increasing the tensile strength and elongation in the presence of convection; thiourea derivatives also have the effect of promoting deposition, reducing the surface roughness of the copper foil, and increasing the tensile strength and elongation;
[0027] (2) The self-made tetrahydrothiazolidinethione dispersion of the present invention can promote the deposition and anodic dissolution process of copper ions, act as a "charge transfer bridge", accelerate the valence state conversion of copper, and the self-made tetrahydrothiazolidinethione dispersion has convection-dependent adsorption characteristics, which significantly affects the competitive adsorption process between brighteners, stabilizers and high-resistance agents, and further improves the tensile properties and elongation of copper foil.
[0028] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0029] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0030] A high-elongation tensile additive includes a bright leveling agent, a high-resistance agent and a stabilizer;
[0031] The raw materials of the brightening and leveling agent include one or more of sodium polydisulfide propane sulfonate, sodium N,N-dimethyl-disulfoformamide propane sulfonate, sodium 3-mercaptopropane sulfonate, sodium phenyl polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, collagen aqueous solution, and polyvinyl pyrrolidone; a compound containing a sulfur group is used as a brightening agent, which can form a cuprous complex and adsorb on the copper deposition site to catalyze and promote deposition, thereby reducing the roughness of the copper foil within a certain concentration and increasing the tensile strength and elongation;
[0032] The preparation method of the collagen aqueous solution is as follows: collagen, ethylenediaminetetraacetic acid and water are mixed in a mass ratio of 20:1:179, and then loaded into a stirring device, and stirred and mixed at a speed of 200 to 300 r / min for 20 to 30 minutes, and after the stirring and mixing is completed, the collagen aqueous solution is obtained;
[0033] The high resistance agent is composed of amine derivatives and thiourea derivatives;
[0034] The amine derivative raw material includes one of polyethyleneimine alkyl salt, polyethyleneimine alkyl compound, polyacrylamide, and polyquaternary ammonium salt; wherein the presence of the amine organic matter can promote the adsorption of cations at active sites, enhance the adsorption of unsaturated bonds, and increase cathode polarization, thereby reducing the surface microscopic contour fluctuations, reducing the surface roughness, and increasing the tensile strength and elongation in the presence of convection;
[0035] The thiourea derivative raw material includes one of diethylthiourea, allylthiourea, ethylenethiourea, and isopropylthiourea; the thiourea derivative also has the effect of promoting deposition, reducing the surface roughness of the copper foil, and increasing the tensile strength and elongation;
[0036] The stabilizer is composed of a high resistance stabilizer and an extension stabilizer;
[0037] The raw material of the high resistance stabilizer includes one of a self-made tetrahydrothiazolidinethione dispersion and sodium thiazoline dithiopropane sulfonate;
[0038] The raw material of the extension stabilizer includes one or more of polyethylene glycol, allyl polyethylene glycol, fatty amine polyoxyethylene ether, hydroxyethyl cellulose, and fatty alcohol polyoxyethylene ether.
[0039] The preparation method of the self-made thiazolidinethione dispersion is as follows: thiazolidinethione and concentrated sulfuric acid are mixed at a mass ratio of 1:10 to obtain a mixed solution, the mixed solution is mixed with water at a mass ratio of 1:8, and then allyl polyethylene glycol of the same mass as thiazolidinethione is added, and the mixture is put into an ultrasonic oscillator, and ultrasonically oscillated and mixed at a frequency of 30 kHz for 15 to 20 minutes to obtain a self-made thiazolidinethione dispersion. The self-made thiazolidinethione dispersion of the present invention can promote the deposition and anodic dissolution process of copper ions, act as a "charge transfer bridge", and accelerate the valence state conversion of copper. The self-made thiazolidinethione dispersion has a convection-dependent adsorption characteristic, which significantly affects the competitive adsorption process between the brightener, the stabilizer and the high-resistance agent, and further improves the tensile properties and elongation of the copper foil.
[0040] Example 1
[0041] (1) Collagen, ethylenediaminetetraacetic acid and water are mixed in a mass ratio of 20:1:179, and then loaded into a stirring device, and stirred and mixed at a speed of 200 r / min for 20 minutes, and after the stirring and mixing is completed, a collagen aqueous solution is obtained;
[0042] (2) mixing sodium 3-mercaptopropane sulfonate, sodium phenyl polydisulfide propane sulfonate and the above collagen aqueous solution in a mass ratio of 2:1:50, adding the mixture into a stirring device, and stirring the mixture at a speed of 50 r / min for 30 minutes to obtain a brightening and leveling agent;
[0043] (3) Diethylthiourea and polyacrylamide are mixed in a mass ratio of 1:15 and placed in a stirring tank, and stirred and mixed at a speed of 200 to 300 r / min for 20 minutes to obtain a high resistance agent;
[0044] (4) Thiathiazolidinethione and concentrated sulfuric acid were mixed at a mass ratio of 1:10 to obtain a mixed solution, the mixed solution was mixed with water at a mass ratio of 1:8, and then allyl polyethylene glycol of the same mass as that of tetrahydrothiazolidinethione was added, and the mixture was placed in an ultrasonic oscillator and ultrasonically oscillated and mixed at a frequency of 30 kHz for 15 minutes to obtain a self-made tetrahydrothiazolidinethione dispersion;
[0045] (5) mixing the self-made tetrahydrothiazolidinethione dispersion, allyl polyethylene glycol, fatty alcohol polyoxyethylene ether and hydroxyethyl cellulose in a mass ratio of 50:1:1:1, placing the mixture in a stirring tank, and stirring the mixture at a speed of 100 r / min for 15 min to obtain a stabilizer;
[0046] (6) Mix the brightening and leveling agent, high tensile agent and stabilizer in equal volume ratio to obtain a high elongation and high tensile strength additive;
[0047] (7) When using the high-elongation and high-tensile additive, add the high-elongation and high-tensile additive to the copper foil electrolyte at an addition amount of 0.5 mL / L to electrolyze the lithium-ion copper foil. After the electrolysis is completed, take out the copper foil and bake it at 140°C for 15 minutes to obtain the finished electrolytic copper foil. The parameters of the copper foil electrolyte are: copper ion concentration of 85 g / L, sulfuric acid concentration of 100 g / L, chloride ion concentration of 20 mg / L, and electrolyte flow rate of 50 m / L during electrolysis. 3 / h, current density 20000A / m 2 .
[0048] Example 2
[0049] (1) Collagen, ethylenediaminetetraacetic acid and water are mixed in a mass ratio of 20:1:179, and then loaded into a stirring device, and stirred and mixed at a speed of 250 r / min for 25 minutes, and after the stirring and mixing is completed, a collagen aqueous solution is obtained;
[0050] (2) mixing sodium polydisulfide propane sulfonate, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate and the above collagen aqueous solution in a mass ratio of 2:1:50, adding the mixture into a stirring device, and stirring the mixture at a speed of 55 r / min for 35 minutes to obtain a brightening and leveling agent;
[0051] (3) mixing diethylthiourea and polyethyleneimine alkyl salt in a mass ratio of 1:15 and placing them in a stirring tank, stirring and mixing at a speed of 250 r / min for 25 minutes, and obtaining a high resistance agent after the stirring and mixing is completed;
[0052] (4) Thiathiazolidinethione and concentrated sulfuric acid were mixed at a mass ratio of 1:10 to obtain a mixed solution, the mixed solution was mixed with water at a mass ratio of 1:8, and then allyl polyethylene glycol of the same mass as that of tetrahydrothiazolidinethione was added, and the mixture was placed in an ultrasonic oscillator and ultrasonically oscillated and mixed at a frequency of 30 kHz for 18 minutes to obtain a self-made tetrahydrothiazolidinethione dispersion;
[0053] (5) mixing the self-made tetrahydrothiazolidinethione dispersion, allyl polyethylene glycol, fatty amine polyoxyethylene ether and hydroxyethyl cellulose in a mass ratio of 50:1:1:1, placing the mixture in a stirring tank, and stirring the mixture at a speed of 150 r / min for 18 min to obtain a stabilizer;
[0054] (6) Mix the brightening and leveling agent, high tensile agent and stabilizer in equal volume ratio to obtain a high elongation and high tensile strength additive;
[0055] (7) When using the high-elongation and high-tensile additive, add the high-elongation and high-tensile additive to the copper foil electrolyte at an addition amount of 0.5 mL / L to electrolyze the lithium-ion copper foil. After the electrolysis is completed, take out the copper foil and bake it at 140°C for 15 minutes to obtain the finished electrolytic copper foil. The parameters of the copper foil electrolyte are: copper ion concentration of 85 g / L, sulfuric acid concentration of 100 g / L, chloride ion concentration of 20 mg / L, and electrolyte flow rate of 50 m / L during electrolysis. 3 / h, current density 20000A / m 2 .
[0056] Example 3
[0057] (1) Collagen, ethylenediaminetetraacetic acid and water are mixed in a mass ratio of 20:1:179, and then loaded into a stirring device, and stirred and mixed at a speed of 300 r / min for 30 minutes, and after the stirring and mixing is completed, a collagen aqueous solution is obtained;
[0058] (2) mixing sodium polydisulfide propane sulfonate, polyvinyl pyrrolidone and the above collagen aqueous solution in a mass ratio of 2:1:50, adding the mixture into a stirring device, and stirring the mixture at a speed of 60 r / min for 40 minutes to obtain a brightening and leveling agent;
[0059] (3) mixing allyl thiourea and polyquaternary ammonium salt in a mass ratio of 1:15 and placing them in a stirring tank, stirring and mixing at a speed of 300 r / min for 30 minutes, and obtaining a high resistance agent after the stirring and mixing is completed;
[0060] (4) mixing sodium thiazolyl disulfide propane sulfonate, allyl polyethylene glycol, fatty amine polyoxyethylene ether and hydroxyethyl cellulose, placing the mixture in a stirring tank, and stirring the mixture at a speed of 200 r / min for 20 min to obtain a stabilizer;
[0061] (5) Mix the brightening and leveling agent, high tensile agent and stabilizer in equal volume ratio to obtain a high elongation and high tensile strength additive;
[0062] (6) When using the high-elongation and high-tensile additive, add the high-elongation and high-tensile additive to the copper foil electrolyte at an addition amount of 0.5 mL / L to electrolyze the lithium-ion copper foil. After the electrolysis is completed, take out the copper foil and bake it at 140°C for 15 minutes to obtain the finished electrolytic copper foil. The copper foil electrolyte parameters are: copper ion concentration of 85 g / L, sulfuric acid concentration of 100 g / L, chloride ion concentration of 20 mg / L, and electrolyte flow rate of 50 m / L during electrolysis. 3 / h, current density 20000A / m 2 .
[0063] Comparison Example
[0064] Comparative Example 1: This comparative example is basically the same as Example 2, except that the self-made thiazolidinethione dispersion is not added to the stabilizer, and an electrolytic copper foil is also prepared;
[0065] The performance tests were conducted on the electrolytic copper foils prepared in Examples 1 to 3 of the present invention and Comparative Example 1. The specific test results are shown in Table 1:
[0066] Table 1 Performance test results
[0067] Test items Tensile strength(MPa) Elongation(%) Example 1 548 17 Example 2 550 18 Example 3 547 16 Comparative Example 1 495 12
[0068] It can be seen from the test data in the above table that the tensile strength of the electrolytic copper foil prepared in Examples 1-3 of the present invention exceeds 540Mpa, and the elongation exceeds 15%, which proves that the technical solution of the present application is highly feasible;
[0069] Comparing the control example 1 with the embodiment of the present invention, since the self-made thiazolidinethione dispersion was not added in the control example 1, the electrolytic copper foil was also prepared, but the tensile strength and elongation of the final electrolytic copper foil were significantly reduced. It can be confirmed that the self-made thiazolidinethione dispersion of the present invention can promote the deposition and anodic dissolution process of copper ions, act as a "charge transfer bridge", accelerate the valence state conversion of copper, and the self-made thiazolidinethione dispersion has convection-dependent adsorption characteristics, which significantly affects the competitive adsorption process between the brightener, stabilizer and high-resistance agent, and further improves the tensile properties and elongation of the copper foil.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the technical principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a high-elongation and high-tensile additive, characterized in that: The specific preparation steps are: (1) Collagen, ethylenediaminetetraacetic acid and water are mixed in a mass ratio of 20:1:179, and then loaded into a stirring device, and stirred and mixed at a speed of 200 r / min for 20 minutes, and after the stirring and mixing is completed, a collagen aqueous solution is obtained; (2) mixing sodium 3-mercaptopropane sulfonate, sodium phenyl polydisulfide propane sulfonate and the above collagen aqueous solution in a mass ratio of 2:1:50, adding the mixture into a stirring device, and stirring the mixture at a speed of 50 r / min for 30 minutes to obtain a brightening and leveling agent; (3) Diethylthiourea and polyacrylamide are mixed in a mass ratio of 1:15 and placed in a stirring tank, and stirred and mixed at a speed of 200 to 300 r / min for 20 minutes to obtain a high resistance agent; (4) Thiathiazolidinethione and concentrated sulfuric acid were mixed at a mass ratio of 1:10 to obtain a mixed solution, the mixed solution was mixed with water at a mass ratio of 1:8, and then allyl polyethylene glycol of the same mass as that of tetrahydrothiazolidinethione was added, and the mixture was placed in an ultrasonic oscillator and ultrasonically oscillated and mixed at a frequency of 30 kHz for 15 minutes to obtain a self-made tetrahydrothiazolidinethione dispersion; (5) mixing the self-made tetrahydrothiazolidinethione dispersion, allyl polyethylene glycol, fatty alcohol polyoxyethylene ether and hydroxyethyl cellulose in a mass ratio of 50:1:1:1, placing the mixture in a stirring tank, and stirring the mixture at a speed of 100 r / min for 15 min to obtain a stabilizer; (6) The brightening and leveling agent, high tensile strength agent and stabilizer are mixed evenly in equal volume ratios to obtain a high elongation and high tensile strength additive.
2. The method for applying a high elongation and high tensile strength additive according to claim 1, characterized in that The specific application steps are as follows: adding a high elongation and high tensile strength additive to the copper foil electrolyte at an addition amount of 0.5 mL / L, electrolyzing the lithium copper foil, taking out the copper foil after the electrolysis, and baking it at 140°C for 15 minutes to obtain the finished electrolytic copper foil; the parameters of the copper foil electrolyte are as follows: the copper ion concentration is 85 g / L, the sulfuric acid concentration is 100 g / L, the chloride ion concentration is 20 mg / L, and the electrolyte flow rate during electrolysis is 50 m 3 / h, current density 20000A / m 2 .
Citation Information
Patent Citations
Manufacturing method of high-tensile lithium battery copper foil
CN110629257A
Preparation method, product and application of 3.5-micron power lithium battery electrolytic copper foil additive
CN113604845A